Tax Compliance Behaviour of Individuals under Self Assessment System - Sia, Gioak Faa (2008)
Tax non-compliance has always been a major concern for all tax administrations, more so in a self assessment environment where it is dependent on voluntary compliance. In Malaysia, there is a dearth of empirical research on tax compliance in relation to the implementation of self assessment which only began in 2001 for corporations and 2004 for individual taxpayers. One of the objectives for implementing self assessment is to increase voluntary tax compliance. As such, in a tax system based largely on voluntary compliance, understanding factors that affect compliance amongst individual taxpayers is of vital importance. This thesis integrates two important approaches, namely, the economic and behavioral approaches in examining factors affecting tax compliance. The factors examined include perceived probability of detection, prior tax audit, sanction perception, perception of fairness, perceived moral intensity and peer influence. The data for this study were gathered by using a mail survey. Descriptive analysis and multivariate analysis were performed on the data to determine how the above mentioned factors affect tax compliance behavior. The findings showed that four factors, namely, perceived probability of detection, sanction perception, perceived moral intensity and peer influence were found to have significa~t relationships with tax compliance. On the other hand, perception of fairness and prior tax audit were found to have insignificant relationships with tax compliance. However, even though prior tax audit did not have a direct effect on tax compliance, it was found to be significantly associated with perceived probability of detection which is significantly related to tax compliance. This implies that prior tax audit has an indirect effect on tax compliance. Apart from prior tax audit affecting perceived probability of detection, another factor examined namely sanction perception was found to affect perceived probability of detection. In relation to perceived probability of detection and perceived moral intensity which had significant relationships with tax compliance respectively, the findings also indicated that both perceived probability of detection and perceived moral intensity had significant relationships with perception of fairness. Understanding these relationships is important as it not only extends knowledge on improving tax compliance but also provides useful information for the revenue collection authorities in designing better tax policies.